Multidimensional evaluation and service strategy analysis of hazard warning and risk reduction - Cao, Zhiyu; Wang, Jiahe; Liu, Yingjie; Zhao, Jingjing; Song, Yingying; Zhao, Boting (Frontiers in Earth Science, 2024)
To refine the meteorological warning service for decision makers and enhance their role in disaster risk reduction, this paper puts forward the efficiency index for warning on disaster risk reduction by analyzing meteorological warnings. The influence factors of the index are investigated, and an index calculation model is established by using Grey relation analysis. The weights of the evaluation factors are determined by entropy weight method to quantify the efficiency of warning. Additionally, the reminder strength of different warning delivery methods to decision makers is studied, and a refined delivery strategy tree for warnings to decision makers is established based on the efficiency index and reminder strength of delivery means. The proposed strategy has been applied to the warning service system in Fujian Province. Results show that its implementation has improved the efficiency of warning dissemination and reduced delivery warning costs.